Laminated Carbon Based Flexible Printed Perovskite Solar Cells Passivated with Tin(II) Phthalocyanine - Nursultan Mussakhanuly; Yerassyl Yerlanuly; Hryhorii P. Parkhomenko; Adiya Niyetullayeva; Aidana K. Azamat; Assanali Sultanov; Zarina Kukhayeva; Annie Ng; Askhat N. Jumabekov (Advanced Materials Interfaces)
Abstract Production scalability, efficiency, and stability challenges continue to impede the commercial viability of perovskite solar cells (PSCs). In this study, a multifunctional passivation technique is introduced, designed to enhance the efficiency and stability of printable, air‐processed PSCs with laminated carbon electrodes. This findings indicate that tin(II) phthalocyanine (SnPC) molecules act as an interfacial layer between the absorber and the hole‐transporting layer (HTL), effectively passivating surface trap states and facilitating hole extraction. Optimal SnPC surface treatment reduces the trap density in the perovskite layer from 2.1 × 1015 to 1.5 × 1015 cm−3, increases carrier mobility (from 2.7 × 10−3 to 2.8 × 10−3 cm2 Vs−1), and extends carrier lifetime. SEM, AFM, EDS, and XPS analyses confirm the presence of SnPC on the perovskite layer surface and its influence on surface morphology. Devices treated with an optimal SnPC concentration exhibit significant efficiency improvements, from 6.4% to 8.5%, along with a threefold increase in photo‐stability. Thus, SnPC may serve as a passivating buffer layer for the perovskite surface, offering protection against photo‐degradation.